2005
DOI: 10.1002/eji.200425954
|View full text |Cite
|
Sign up to set email alerts
|

Blocking ion channel KCNN4 alleviates the symptoms of experimental autoimmune encephalomyelitis in mice

Abstract: The KCNN4 potassium-ion channel has been reported to play an important role in regulating antigen-induced T cell effector functions in vitro. This study presents the first evidence that a selective KCNN4 blocker, TRAM-34, confers protection against experimental autoimmune encephalomyelitis (EAE) in the mouse model. Treatment with the KCNN4 blocker did not prevent infiltration of T cells in the spinal cord, but resulted in the reduction of both the protein and the message levels of TNF-a and IFN-c as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…Remarkably, in the present issue of European Journal of Immunology, Reich et al [4] from the ScheringPlough Research Institute provide compelling pharmacological evidence that selective blockage of the IK channel with TRAM-34 protects mice against antigeninduced development of EAE. In contrast to the adoptive transfer of T cells, this model relies on immunization by a peptide fragment of the myelin oligodendrocyte glycoprotein ).…”
Section: Consequences Of Pharmacological Blockade Of K + Channels In mentioning
confidence: 88%
See 2 more Smart Citations
“…Remarkably, in the present issue of European Journal of Immunology, Reich et al [4] from the ScheringPlough Research Institute provide compelling pharmacological evidence that selective blockage of the IK channel with TRAM-34 protects mice against antigeninduced development of EAE. In contrast to the adoptive transfer of T cells, this model relies on immunization by a peptide fragment of the myelin oligodendrocyte glycoprotein ).…”
Section: Consequences Of Pharmacological Blockade Of K + Channels In mentioning
confidence: 88%
“…Blockers of both channel types have given promising results in various in vitro assays for T cell activation [1][2][3][4]8]. The gold standard for evaluation of the potential of a new molecular target is, however, to obtain effects in validated animal models such as inhibition of host-graft reactions or animal models of autoimmune diseases, such as multiple sclerosis.…”
Section: Consequences Of Pharmacological Blockade Of K + Channels In mentioning
confidence: 99%
See 1 more Smart Citation
“…Bayer (Wuppertal, Germany) developed several KCa3.1 blockers, tested them in a rat model of traumatic brain injury (subdural hematoma), and found that several hours of intravenous administration of either a triazole or a cyclohexadiene compound significantly reduced the ensuing edema, intracranial pressure, and infarct volume (Mauler et al, 2004). KCa3.1 blockade reduced inflammatory cytokine production and damage in the spinal cord in a murine model of multiple sclerosis (Reich et al, 2005), but potential contributions of CNS cells were not determined. Blocking KCa3.1 channels in endothelia and smooth muscle cells in the rat middle cerebral artery inhibited hyperpolarization and vessel relaxation (McNeish et al, 2006).…”
Section: Broader Implicationsmentioning
confidence: 99%
“…hIK1 has also been shown to play a role in both macrophage activation and T-lymphocyte proliferation (10 -12). The critical role that pharmacological modulation of hIK1 may play has been revealed by the demonstration that blockers of hIK1 reduce the autoimmune response to experimental encephalomyelitis in mice (13), reduce brain edema following traumatic brain injury (14), and prevent restenosis following balloon angioplasty (15). Also, openers have been shown to alter vascular tone and hence may modulate peripheral blood pressure (16,17).…”
mentioning
confidence: 99%